Zn(ferulate)-LSH Systems as Multifunctional Filters - Saito, Gustavo Pereira [UNESP]; Matsumoto, Ana Carolina Lanfredi [UNESP]; Assis, Renata Pires [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Cebim, Marco Aurélio [UNESP]; Davolos, Marian Rosaly [UNESP] (MDPI, 2021)
Excessive UV solar radiation exposure causes human health risks; therefore, the study of multifunctional filters is important to skin UV protective ability and also to other beneficial activities to the human organism, such as reduction of reactive oxygen species (ROS) responsible for cellular damages. Potential multifunctional filters were obtained by intercalating of ferulate anions into layered simple metal hydroxides (LSH) through anion exchange and precipitation at constant pH methods. Ultrasound treatment was used in order to investigate the structural changes in LSH-ferulate materials. Structural and spectroscopic analyses show the formation of layered materials composed by a mixture of LSH intercalated with ferulate anions, where carboxylate groups of ferulate species interact with LSH layers. UV-VIS absorption spectra and in vitro SPF measurements indicate that LSH-ferulate systems have UV shielding capacity, mainly UVB protection. The results of reactive species assays show the ability of layered compounds in capture DPPH•, ABTS•+, ROO•, and HOCl/OCl- reactive species. LSH-ferulate materials exhibit antioxidant activity and singular optical properties that enable their use as multifunctional filters.
Keywords: antioxidant activity; hydroxycinnamic anions; intercalation; layered single metal hydroxides; ultrasound treatment; UV protection